Pengelolaan Sumber Daya Manusia Dalam Mencapai Sekolah Adiwiyata Di Sekolah Dasar Negeri 4 Sragen Kabupaten Sragen - MURSITO, Mursito, Prof. Dr. Budi Murtiyasa, M.Kom, Dr. Sabar Narimo, M.M., M.Pd (2015)
The aim of research carried out at the State Primary School 4 Sragen Sragen. To describe: 1) the development of human resources (HR) in achieving elementary schools in the State Adiwiyata 4 Sragen. 2) problems in the schoolrelated human resource management in achieving elementary schools in the State Adiwiyata 4 Sragen. 3) efforts to overcome the obstacles faced by schools in the management of human resources in achieving elementary schools in the State Adiwiyata 4 Sragen. This study uses a qualitative method. Data were collected through interviews, observation and documentation. The validity of the data using credibility. Data were analyzed interactively and continues over time until complete, so the data is saturated. Results of research on the development of human resources in achieving the school Adiwiyata 1) stages of human resources management in realizing the school adi Wiyata: a. Identification of competencies / talents of teachers and other staff; b. Placement of teachers and other staff adjusted the assessed aspects; c. Socialization and training Adiwiyata school program ,; d. Implementation and evaluation of school programs Adiwiyata; e. Improvement and development of school programs Adiwiyata. f. Giving honor attendant Adiwiyata school program; g. Dismissal / replacement school program officer Adiwiyata 2) Constraints faced in running Adiwiyata program are: a. Adi Wiyata program is a new program needs to be an understanding and knowledge by all parties. b. Adi Wiyata program aims to change behavior that is difficult to apply in primary schools. Many factors that cause obstacles in realizing Wiyata adi school both from internal and external saekolah school. 3) Steps need to be taken because the constraints of teachers among other elements: 1) the call will use waste sorting 2) the need for clarification on the role and function of teachers picket duty. Steps need to be taken because the constraints of the guard element 1) call a special chamber to be directed 2) Assignment of part Sarpras check PAM installation and use of electrical house keeper. Steps need to be taken related constraints of students, among other elements: 1) establish special forces Pasdan name (Forces Model) which should monitor plants that seemed to wilt / untreated. 2) special attention to children with disabilities (lazy) to be assisted in maintaining the cleanliness of the environment. 3) Making a statement relating to the infringement.